Facebook como herramienta de comunicación política de los candidatos a la Prefectura de Zamora Chinchipe, y su incidencia en las elecciones de 2023. - Cordero Carrión, Ximena Marianela (2024)
This thesis work focuses on conducting a study on "Facebook as a tool for political communication by candidates for the Prefecture of Zamora Chinchipe and its impact on the 2023 elections." The methodological approach was of a mixed nature, combining qualitative and quantitative methods through a description and analysis aimed at determining the relationship between two or more variables using statistical information. The target population for this research comprised the followers of the candidate's pages under study: 13 thousand followers of Karla Reátegui's fan page and 9.1 thousand of Bladimir Armijos'. An unstructured observation sheet was developed to extract the posts from both candidates' fan pages, aiming to establish the level of engagement achieved. Additionally, interviews were conducted with the campaign advisors of the candidates, as these two professionals were responsible for directing the strategies of the political campaigns conducted on social media platforms, specifically Facebook. Following the application of data collection instruments, it was identified that the candidates utilized the Facebook social network to positively position their image and thereby attract new voters who resonated with their proposals and personal characteristics. Another crucial aspect of this research was the relationship between the effective use of Facebook and success in the campaign. The candidates employed the platform effectively to establish representativity, build visibility, and shape their digital identity, predominantly by posting content of an emotional, sentimental, and biographical nature. The winning candidate achieved higher interaction on the platform by adopting a close and spontaneous tone in her communication with the audience. Finally, this study provides a detailed insight into how both candidates leveraged this social network during the open campaign. It also offers a robust framework that directs and guides future studies on political communication in social networks.